The relationship between child eating behaviour with body mass index among toddlers aged two to four years old - Hassan, N.E.; Arepen, A.M.; Baharom, N.; Rani, M.D.M.; Juliana, N.; Faizul Helmi Addnan; Nur Fariha Mohd Manzor; Nazefah Abdul Hamid (J. K. Welfare and Pharmascope Foundation, 2024)
Indexed by Scopus